Evaluation of the antioxidant capacity of sweet potato (Ipomoea batatas) - Obille, Ma. Elisa Viacrusis (2007)
ABSTRACT Locally available root crops, such as sweet potato, may contain antioxidants that are capable of scavenging free radicals and other reactive species which are responsible for biological damage. In order to evaluate the antioxidant capacity of sweet potato, several tests were conducted. In this study, four varieties of sweet potato: VSP 6, Emitlog, Peke Negro and Emelda, were evaluated for total phenolic content, DPPH radical scavenging, ferrous ion chelating, reducing power and total antioxidant activity tests. Total antioxidant capacity showed the order of VSP 6> Emitlog > Emelda > Peke Negro. The total phenolic content ranged between 62.604 to 101.371 mg GAE/100g dry samples and was significantly positively correlated with the antioxidant activity. DPPH radical scavenging activity, ferrous ion chelating and reducing power were negatively correlated with antioxidant activity. Ferrous ion chelating and reducing power of the sweet potato extracts measured in this study were very low.